(untitled) (Homiletic, 2010)
Howard Thurman receives little mention in many contemporary discussions on preaching. Yet, his era recognized – at least in part – his homiletical genius. In 1953, Thurman was named one of the twelve greatest preachers in the United States by Life Magazine. The field of homiletics still has much to gain by revisiting Thurman’s genius in preaching. For Thurman, preaching is more than an exercise that gives voice to biblical, theological, doctrinal, and social studies. Thurman views preaching as an act of spirit. This is the thesis I uphold in this paper. First, I will broach briefly the significance of Thurman by traversing his professional accomplishments. Second, I will expose the basic tenants of Thurman’s homiletical theory. Finally, I will suggest implications for Thurman’s integration into homiletical study.